Histone Deacetylase 6 as a Therapeutic Target in B cell-associated Hematological Malignancies - Yang, Jia; Li, Dengwen; Zhou, Jun (Frontiers in Pharmacology, 2020)
B lymphocytes play a critical role in humoral immunity. Abnormal B cell development and function cause a variety of hematological malignancies such as myeloma, B cell lymphoma, and leukemia. Histone deacetylase 6 (HDAC6) inhibitors alone or in combination with other drugs have shown efficacy in several hematological malignancies, including those resistant to targeted therapies. Mechanistically, HDAC6 inhibitors promote malignant tumor cell apoptosis by inhibiting protein degradation, reinvigorating anti-tumor immunity, and inhibiting cell survival signaling pathways. Due to their specificity, HDAC6 inhibitors represent a very promising and feasible new development pipeline for high-efficacy drugs with limited side effects. This article reviews recent progress in the mechanisms of action of HDAC6 inhibitors for the treatment of B cell-associated hematological malignancies, such as multiple myeloma and B cell non-Hodgkin lymphoma, which are often resistant to targeted therapies.